Pain Management in the Clinical Practice with Non-Pharmacological Therapy Warm Compress: Systematic Review” - Junianto Junianto; Sidik Awaludin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pain is a distressing sensory and emotional experience caused by tissue damage. Pain management can be pharmacological or non-pharmacological, with warm compress therapy as a supportive treatment to reduce pain scores. This study aims to analyse the effectiveness of warm compress therapy in pain management. This Systematic Review includes articles from Science Direct, PubMed, Cochrane Library, and Google Scholar (2014-2024). Article assessment was conducted using the Joanna Briggs Institute instrument, with inclusion criteria based on PICOS: pain patients (P), warm compress intervention (I), control group (C), pain score reduction (O), and RCT studies (S). Based on 10 reviewed articles, warm compress therapy is applied through various methods, including hot compresses, electric heating pads, warm water bags, Chinese herbs, infrared belts, and sterile towels. Besides pain reduction, this therapy improves blood circulation, relaxes muscles, and reduces anxiety. Warm compress therapy is recommended as a non-pharmacological approach to pain management.